Soluble CD40 Ligand Levels in Otherwise Healthy Subjects With Impaired Fasting Glucose - Ilker Tasci; Teoman Dogru; Alper Sonmez; Halil Genc; Selim Kilic; Abdullah Olgun; Mahmut Gok; Gokhan Erdem; Selahattin Erikci (Mediators of Inflammation)
Unlike diabetes mellitus and impaired glucose tolerance, it is not clear whether the subjects with impaired fasting glucose (IFG) are at increased risk of atherosclerosis and cardiovascular diseases. The CD40-CD40 ligand interaction is involved in the mechanism of atherosclerosis. We investigated whether soluble CD40L (sCD40L) as well as high sensitive C-reactive protein (hsCRP) levels are increased in subjects with IFG having no confounding factors for inflammation or atherosclerosis. Twenty four IFG subjects with no additional disorders and 40 appropriate healthy controls were studied. sCD40L and hsCRP levels in the IFG and control groups were similar. Blood pressures, total and LDL-cholesterol, and triglyceride levels were also similar, whereas HDL-cholesterol was lower and HOMA-IR indexes were higher in the IFG group. Though the sample size was small, the present data show that sCD40L seems not to alter in subjects with IFG suggesting that it might not be an independent risk factor for atherosclerosis.